Analisis Geometri Jalan menggunakan Perangkat Lunak Civil 3D di Jalan Leo Mamiri Kabupaten Mimika, Provinsi Papua Tengah - Item, Reinaldo; Julians, Adhe Ronny; Habar, Atanasius Gunsah (Lembaga Yasin AlSys, 2025)
The limited number of studies on the application of Building Information Modeling (BIM)-based software in road geometry analysis, particularly in Central Papua with its diverse topography, underlies this research. Compliance of road geometry with national standards is crucial as it directly affects user safety and comfort. This study aims to analyze the geometric conformity of Jalan Leo Mamiri, Mimika Regency, using Autodesk Civil 3D software. A quantitative approach was applied through geometric modeling based on topographic survey data, analyzed using the horizontal alignment, vertical profile, and cross section features in Civil 3D. The findings show that several road segments do not meet geometric standards, especially at curves with small radii and longitudinal slopes exceeding the maximum threshold. These results highlight the importance of aligning road design with national standards to minimize traffic accident risks. The study concludes that Autodesk Civil 3D is effective as an analytical and visualization tool in road planning and evaluation. The implications include theoretical contributions in enriching the literature on modeling software applications in transportation engineering and practical contributions in providing recommendations for road planners, contractors, and local governments to support infrastructure development that is safe, efficient, and compliant with standards. Keywords: Road Geometry; Autodesk Civil 3D; Horizontal Alignment; Vertical Profile; Transportation Infrastructure